Topographic Data Acquisition for the VERITAS 2023 Iceland Field Campaign - Mazarico, E.; Nunes, Daniel; Cascioli, G.; Smrekar, S.; Andrews-Hanna, Jeff; Müller, N.; Iess, L.; Domac, Akin; Whitten, Jennifer L.; Buczkowski, D.L.; Jozwiak, L. M.; Di Achille, Gaetano; et al. (2024)
The NASA Discovery mission VERITAS (Venus Emissivity, Radio Science, InSAR, Topography, and Spectroscopy) will explore Venus in the early 2030s, acquiring foundational global datasets that will reshape our understanding of planetary evolution [1]. In addition to a gravity science investigation [2] and a near-infrared spectrometer (VEM) [3], a synthetic aperture radar (VISAR) [4] will globally map the surface at X-band wavelength (~4 cm). To better interpret the radar backscatter measurements, relate them to physical properties such as surface roughness, and intercompare them with other radar datasets (Magellan S-band and EnVision VenSAR S-band), the VERITAS science team conducted a field campaign in Iceland, in collaboration with a multi-band radar mapping airborne campaign by the German Aerospace Center (DLR) [5,6].